Spine Fractures in Ankylosing Spondylitis Patients: Analysis of Fracture Pattern, Clinical, and Radiological Outcome: A Retrospective Observational Study - Shreya P Shenoy; Delhibabu B Thamba; Subhadeep Ghosh; CS Vishnu Prasath; V Venkatasujith (Journal of Orthopedics and Joint Surgery)
Introduction: Spine fractures in patients with ankylosing spondylitis (AS) frequently result from even a low energy mechanism and are associated with spinal cord injury in over 29–91%. The aim of this study is to analyze the pattern, clinical, and radiological outcomes of spine fractures in such patients. Materials and methods: We reviewed 18 patients suffering from AS who sustained a spinal fracture and were treated between 2014 and 2022. Injury mechanism, method of diagnosis, the location and the type of the fracture, neurological status pre and postoperatively (post-op), and management and clinical outcome were studied. Seven of them were diagnosed in X-rays at the initial examination, and the remaining 11 in magnetic resonance imaging (MRI)/computed tomography (CT). Fracture healing and neurological function recovery were observed over the follow-up period. Results: A total of 18 patients were included, all male, with AS, who presented with spine fractures and neurological impairment. The most common level of the spine involved was the thoracolumbar spine (66.66%). Diagnosis of fractures was possible with X-rays only in 31% of cases. The most common pattern of fracture was found to be a chance fracture (33.33%). A total of 13 cases presented varying grades of neurological deficits (72.2%). The neurological function and fracture healing of these patients improved significantly after surgery. The conservatively treated patient had a poor prognosis, and one of the cervical fractures surgically treated patients had respiratory complications. Conclusion: The diagnosis of spine fracture in AS requires higher imaging modalities. Since most cases present with neurological deficits, surgery is required for treatment and has shown to be effective in improving neurological deficits.